A Large Cavernous Sinus Giant Cell Tumor Invading Clivus and Sphenoid Sinus Masquerading as Meningioma: A Case Report and Literature Review - Hu, Shasha; Cheng, Shaowen; Wu, Yu; Wang, Yanyan; Li, XinNian; Zheng, Jiaxuan; Li, Jiao; Peng, Lei; Yang, Jian (Frontiers in Surgery, 2022)
Giant cell tumor (GCT) of the bone is a rare benign, locally aggressive tumor that occurs in the epiphysis of long bones, especially the lower femur and the upper tibia. GCT of the bone of cranial origin is very rare, accounting for 1% of all GCT of the bone. We report the diagnosis, treatment, and immunohistochemistry of a rare case of intracranial GCT of the bone. We also review and summarize the imaging features, diagnostic markers, and current major treatment options for GCT of the bone. Our case and literature review emphasizes the importance of considering the full picture when making a diagnosis, rather than relying on imaging alone to make the diagnosis.